Situation Report: Romania, 24 February 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Coverage of President Nixon's Message Academy of Social and Political Sciences Constituted Shortcomings in Foreign Trade New Profit-Sharing System Miscellaneous